The seven husbands of Evelyn Hugo - ٌReid, Taylor Jenkins (London Simon & Schusrer, 2017)
"The Seven Husbands of Evelyn Hugo" is a captivating novel by Taylor Jenkins Reid that revolves around the fictional life of a Hollywood icon, Evelyn Hugo. The novel is framed as a biography, where an aging Evelyn Hugo, who has been a major star of the Golden Age of Hollywood, recounts her life story to a young, relatively unknown journalist named Monique Grant. <div data-message-author-role="assistant" data-message-id="b666d572-818d-4559-a48d-4f572aeeb870" dir="auto" class="min-h-[20px] text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words [.text-message+&]:mt-5"> Evelyn opens up about her seven marriages, the rise and fall of her career, and her deepest, most intimate secrets, including her complex relationship with her greatest love, who happens to not be any of her husbands. Each chapter in the novel delves into one of her seven marriages, but more importantly, it explores her fierce ambition, personal sacrifices, and the pressures of being a woman in Hollywood during the 1950s to the 1980s. As Evelyn narrates her life story, the novel touches upon significant themes such as identity, the intersection of fame and privacy, sexual fluidity, and the cost of living a life on your terms.Evelyn’s personal revelations include a deep and authentic love story with fellow actress Celia St. James, and this relationship is central to the novel's exploration of LGBTQ+ themes. Throughout the novel, Reid portrays Evelyn as a morally complex character—neither a hero nor a villain—whose choices, however ruthless or self-serving, were shaped by her circumstances and her desire to succeed in an industry dominated by men.Monique, who is dealing with her own personal struggles, soon realizes that she has a profound connection to Evelyn’s story, which ultimately leads to a twist that reshapes her understanding of her own life and the narrative Evelyn has shared.Reid’s novel is more than just a tale of scandalous marriages and celebrity culture. It’s a poignant reflection on love, fame, and the lengths people go to in order to protect their true selves. It is as much about the resilience and vulnerability of one woman’s journey through life as it is a commentary on the choices women make, particularly in male-dominated fields like Hollywood."The Seven Husbands of Evelyn Hugo" has received critical acclaim for its rich character development, its portrayal of LGBTQ+ relationships, and its ability to evoke the glamour and heartbreak of old Hollywood. It’s a story of reinvention, resilience, and empowerment, appealing to both fans of historical fiction and contemporary literary fiction. <path fill-rule="evenodd" clip-rule="evenodd" d="M11 4.9099C11 4.47485 10.4828 4.24734 10.1621 4.54132L6.67572 7.7372C6.49129 7.90626 6.25019 8.00005 6 8.00005H4C3.44772 8.00005 3 8.44776 3 9.00005V15C3 15.5523 3.44772 16 4 16H6C6.25019 16 6.49129 16.0938 6.67572 16.2629L10.1621 19.4588C10.4828 19.7527 11 19.5252 11 19.0902V4.9099ZM8.81069 3.06701C10.4142 1.59714 13 2.73463 13 4.9099V19.0902C13 21.2655 10.4142 22.403 8.81069 20.9331L5.61102 18H4C2.34315 18 1 16.6569 1 15V9.00005C1 7.34319 2.34315 6.00005 4 6.00005H5.61102L8.81069 3.06701ZM20.3166 6.35665C20.8019 6.09313 21.409 6.27296 21.6725 6.75833C22.5191 8.3176 22.9996 10.1042 22.9996 12.0001C22.9996 13.8507 22.5418 15.5974 21.7323 17.1302C21.4744 17.6185 20.8695 17.8054 20.3811 17.5475C19.8927 17.2896 19.7059 16.6846 19.9638 16.1962C20.6249 14.9444 20.9996 13.5175 20.9996 12.0001C20.9996 10.4458 20.6064 8.98627 19.9149 7.71262C19.6514 7.22726 19.8312 6.62017 20.3166 6.35665ZM15.7994 7.90049C16.241 7.5688 16.8679 7.65789 17.1995 8.09947C18.0156 9.18593 18.4996 10.5379 18.4996 12.0001C18.4996 13.3127 18.1094 14.5372 17.4385 15.5604C17.1357 16.0222 16.5158 16.1511 16.0539 15.8483C15.5921 15.5455 15.4632 14.9255 15.766 14.4637C16.2298 13.7564 16.4996 12.9113 16.4996 12.0001C16.4996 10.9859 16.1653 10.0526 15.6004 9.30063C15.2687 8.85905 15.3578 8.23218 15.7994 7.90049Z" fill="currentColor"> <path fill-rule="evenodd" clip-rule="evenod